1980
DOI: 10.1128/aem.40.2.352-357.1980
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Aspergillus growth and aflatoxin release by derivatives of benzoic acid

Abstract: A study was conducted to determine the effects of o-nitrobenzoate, p-aminobenzoate, benzocaine (ethyl aminobenzoate), ethyl benzoate, methyl benzoate, salicylic acid (o-hydroxybenzoate), trans-cinnamic acid (,B-phenylacrylic acid), trans-cinnamaldehyde (3-phenylpropenal), ferulic acid (p-hydroxy-3-methoxycinnamic acid), aspirin (o-acetoxy benzoic acid), and anthranilic acid (o-aminobenzoic acid) upon growth and aflatoxin release in Aspergillus flavus NRRL 3145 and A. parasiticus NRRL 3240. A chemically defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(32 citation statements)
references
References 22 publications
3
29
0
Order By: Relevance
“…Mycelial growth was separated from the liquid phase by filtering through Aflatoxins were then extracted from the filtrate and quantified according to a previously reported procedure (Chipley and Uraih 1980).…”
Section: Growth Mediummentioning
confidence: 99%
“…Mycelial growth was separated from the liquid phase by filtering through Aflatoxins were then extracted from the filtrate and quantified according to a previously reported procedure (Chipley and Uraih 1980).…”
Section: Growth Mediummentioning
confidence: 99%
“…1977; Beuchat and Jones 1978; Ahmand 1979; Lin and Fung 1983). The ester of p ‐hydroxybenzoic acid (propyl paraben) has been reported to have strong fungicidal activity (Chipley and Uraih 1980). Studies by Thompson (1991, 1992) suggested that phenolic antioxidants could control conidial germination, growth and aflatoxin production by A. flavus and A. parasiticus .…”
Section: Introductionmentioning
confidence: 99%
“…As alternative preservatives, fumaric acid (Pilone et al 1974;Splittstoesser and Stoyla 1989), decanoic acid (Splittstoesser and Stoyla 1989), dimethyl dicarbonate (Porter and Ough 1982) and nisin (Splittstoesser and Stoyla 1989;Radler 1990;Daeschel et al 1991) all, to some degree, inhibit micro-organisms in beverages, but none is permitted for use in these products. On the other hand, the non-flavonoid fraction of grape juice and of wines is rich in derivatives of hydroxycinnamic acids (Ong and Nagel 1978a;Baranowski and Nagel 1981;Herrmann 1989) and some of the free acids have been found to be inhibitory to the growth of a variety of micro-organisms including yeasts (Schanderl 1962;Sikovec 1966a,b;Baranowski et al 1980), moulds (Chipley and Uraih 1980), Escherichia coli, Staphylococcus aureus, Bacillus cereus (Herald and Davidson 1983) and rumen micro-organisms (Chesson et al 1982), but to have little effect on Pseudomonas Juorescens (Baranowski and Nagel 1982) and none on Ltsterra monocytogenes (Payne el al. 1989).…”
Section: Introductionmentioning
confidence: 99%